1999
DOI: 10.1034/j.1600-0420.1999.770204.x
|View full text |Cite
|
Sign up to set email alerts
|

Disc hemorrhage and peripapillary atrophy in apparently healthy subjects

Abstract: ABSTRACT.Purpose: We estimated the prevalence of disc hemorrhage and peripapillary atrophy in apparently healthy subjects. Methods: We reviewed consecutive plain color fundus photographs of 12,140 eyes of 6,070 subjects (male/femaleΩ4,079/1,991) who visited a health consultation center. Results: We analyzed 11,934 eyes of 5,967 subjects with good quality of photographs. Disc hemorrhage was found in 36 eyes of 35 subjects (0.6%). The prevalence of disc hemorrhage was significantly greater in women 60 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
1
11
2
Order By: Relevance
“…Among all participants in the current study, the prevalence of DHs was 1.2% by person, which is markedly higher than that reported in previous health-care-based studies in Japan (0.2 12 and 0.6%, 13 respectively, by person), but it is comparable to that in Australia (1.4% by person), 1 the United States (0.9% by person), 3 and China (1.2% by eye). 6 Among patients with glaucoma, DHs were found in 16.2% in the current study, which is twice as high as that in the Japanese health-carebased study (8.2%) 13 and slightly higher than that in Australia (13.9%), 1 China (10.6%), 6 India (7.4% by person), 5 and a Hispanic population (7.4% by person).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Among all participants in the current study, the prevalence of DHs was 1.2% by person, which is markedly higher than that reported in previous health-care-based studies in Japan (0.2 12 and 0.6%, 13 respectively, by person), but it is comparable to that in Australia (1.4% by person), 1 the United States (0.9% by person), 3 and China (1.2% by eye). 6 Among patients with glaucoma, DHs were found in 16.2% in the current study, which is twice as high as that in the Japanese health-carebased study (8.2%) 13 and slightly higher than that in Australia (13.9%), 1 China (10.6%), 6 India (7.4% by person), 5 and a Hispanic population (7.4% by person).…”
Section: Discussioncontrasting
confidence: 47%
“…[7][8][9][10][11] In Japan, however, no population-based study has been carried out on the prevalence of DHs, although two groups of investigators 12,13 have reported the prevalence of DHs among large numbers of self-participating subjects in health-care programmes. Between these studies, the prevalence of DHs among healthy subjects or those without glaucoma differed substantially, ie, 0.59% (35/5967 subjects) 12 and 0.17% (23/ 13 172 subjects). 13 Moreover, the prevalence of DHs reported in these studies was considerably lower than that in population-based studies including the Blue Mountains Study (prevalence, 1.0%), 1 the Beaver Dam Study (0.9%), 3 and the Beijing Eye Study (1.0%).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to findings in several previous studies. 2,3,12 In glaucoma cases, disc hemorrhages occurred more frequently in the inferotemporal and superotemporal regions. This is also consistent with previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…3,10,11 They include the tendency to develop in the temporal inferior quadrant, 2 in glaucoma eyes with a relatively low intraocular pressure, 2,6,9 especially in the area adjacent to a rim notching, and in females at age 60 years or older. 12 Several investigators [13][14][15][16] have emphasized the pathogenic role of disc hemorrhages in glaucomatous optic neuropathy, while some researchers 17,18 believe that disc hemorrhage is unrelated to glaucoma progression. Drance et al 13 pointed out that visual field defects are more likely to progress in eyes with a disc hemorrhage in chronic simple glaucoma.…”
mentioning
confidence: 99%
“…An association between DHs and peripapillary atrophy has been reported, with DHs tending to occur in eyes with peripapillary atrophy and within areas of its greatest width [10,[24][25][26]. Since peripapillary choroid plays a role in the vascular supply to the prelaminar portion of the ONH, Ahn et al suggest ischemia to be the cause of DHs [10].…”
Section: Discussionmentioning
confidence: 92%